(3TQM GdbUjOI GdHGFjg ddSjO GdMejQis - (3dCHi GdbGSe Ydj Hf GdMSjf Hf ehSi GdTQja GdeQJVis; (3CHh gGTe ESeGYjd Hf eMeO Hf eaQZ, GdMejQj,J (B173 (3g` s
(3ChdgG (B:s
(3SCd GdSjO GdhdO , CWGd Gddg HbGAg , JaSjQ bUjOg CHj gGTe ESeGYjd GdHGFjg GdJi ChdgG hEjVGM eYGfjgG hTcd CdaGXgG s
(3BNQgG (B:s
(3hYJOg Yde GdcJGH hYde eGde jcJH (B: (3ajMJed CeQjf CMOgeG Cf jQjO HGdcJGH eGcJHg ai GddhM GdeMahX hGdhLg GdCNQ jQjO HGdcJGH GdbQBf JeJ GdbUjOI HTQMgG s
(3Jedc eDQN Sfg (B1354(3g` hhba eDQN Sfg (B1377(3g` hHBNQ UaMGJgG JYbjHgs
(3HChdgG eWGdYg eDQNg Sfg (B931(3g`s
(3GdSjO GdMejQi gh CHh gGTe ESeGYjd Hf eMeO Hf eaQZ GdMejQi GdeJhai (B173(3g`s
(3GfXQ ai GdLRA GdChd Qbe (B660 (3COHs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs